Interventionsprogramme und Förderkonzepte für Kinder mit besonderen Schwierigkeiten beim Erlernen des Rechnens (mathematica didactica, 2023)
Problems in learning mathematics, especially in learning arithmetic, are a widespread phenomenon. Attributions such as "dyscalculia" convey the idea of unchangeable dispositions and an orientation towards deficits. Mathematics didactic approaches, on the other hand, are more potential-oriented. Overcoming particular difficulties in learning arithmetic is the focus of this topic. The contributions draw a multi-layered picture of intervention programs and support-concepts that are integrated into or supplement lessons. The focus is drawn especially, but not only, to the primary level.